Heterologous investigation of metabotropic and ionotropic odorant receptors in ab3A neurons of Drosophila melanogaster - Pettersson, Johan Henning; Cattaneo, Alberto Maria (Frontiers in Molecular Biosciences, 2024)
In insects, antennal ionotropic receptors (IRs) and odorant receptors (ORs) are among the main sensors of olfactory cues. To functionally characterize subunits from these receptors, the use of ab3A neurons from transgenic Drosophila melanogaster represented one of the most powerful tools, allowing the identification of ligands (deorphanization) and decrypting their pharmacological properties. However, further investigation is needed to shed light on possible metabotropic functionalities behind insect olfactory receptors and to test potentials from the up to now used empty neuronal systems to express subunits belonging to variegate receptor classes. In this project, we adopted the most updated system of Drosophila ab3A empty neurons to test various olfactory receptors, spacing from human ORs working as metabotropic G-protein coupled receptors (GPCRs), to insect ionotropic IRs and ORs. Testing transgenic Drosophila expressing human ORs into ab3A-neurons by single sensillum recording (SSR) did not result in an OR-response to ligands but it rather re-established neuronal spiking from the empty neurons. When transgenic D. melanogaster expressed ionotropic IRs and ORs, both heterologous and cis-expressed IRs were non-functional, but the D. suzukii OR19A1 subunit responded to a wide asset of ligands, distinguishing phasic or tonic compound-dependent effects. Despite the use of Drosophila ab3A neurons to test activation of some metabotropic and ionotropic receptor subunits resulted non-functional, this study deorphanized a key ORs of D. suzukii demonstrating its binding to alcohols, ketones, terpenes and esters.